(untitled) (Global Journal of Science Frontier Research, 2012)
In the present paper we first establish three new theorems, which involves I-function and general class of polynomials. Next, we obtain certain new integrals and expansion formulas by the application of our theorems. By giving suitable values to the parameters, main integral reduces to Fox’s H-function, G-function and generalized wright hypergeometric function, etc.